The role of infarct transmural extent in infarct extension: A computational study. (9th June 2016) - Leong, Chin‐Neng; Lim, Einly; Andriyana, Andri; Al Abed, Amr; Lovell, Nigel Hamilton; Hayward, Christopher; Hamilton‐Craig, Christian; Dokos, Socrates
Summary: Infarct extension, a process involving progressive extension of the infarct zone (IZ) into the normally perfused border zone (BZ), leads to continuous degradation of the myocardial function and adverse remodelling. Despite carrying a high risk of mortality, detailed understanding of the mechanisms leading to BZ hypoxia and infarct extension remains unexplored. In the present study, we developed a 3D truncated ellipsoidal left ventricular model incorporating realistic electromechanical properties and fibre orientation to examine the mechanical interaction among the remote, infarct and BZs in the presence of varying infarct transmural extent (TME). Localized highly abnormal systolic fibre stress was observed at the BZ, owing to the simultaneous presence of moderately increased stiffness and fibre strain at this region, caused by the mechanical tethering effect imposed by the overstretched IZ. Our simulations also demonstrated the greatest tethering effect and stress in BZ regions with fibre direction tangential to the BZ–remote zone boundary. This can be explained by the lower stiffness in the cross‐fibre direction, which gave rise to a greater stretching of the IZ in this direction. The average fibre strain of the IZ, as well as the maximum stress in the sub‐endocardial layer, increased steeply from 10% to 50% infarct TME, and slower thereafter. Based on our stress–strain loop analysis, we found impairment in the myocardial energy efficiency and elevated energy expenditure with increasing infarct TME, which we believe to place the BZ at further risk of hypoxia. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This work examines the mechanical interaction between the viable and ischemic myocardium in the presence of varying infarct transmural extent to better understand the mechanisms leading to infarct extension. Simulations using a 3D electromechanical model incorporating realistic fibre orientation demonstrated localized highly abnormal systolic fibre stress at the border zone, owing to the simultaneous presence of high strain and stiffness at this region. Apart from elevating fibre stress at the border zone through mechanical tethering imposed by the infarct zone, increasing infarct transmural extent also increases energy expenditure and reduces energy efficiency.